The Role of Business Ethics in Improving Corporate Social Responsibility - Miko, Jeroh (YASIN, 2025)
The inadequate integration of ethical principles into corporate social responsibility (CSR) practices remains a persistent challenge, undermining public trust and long-term business sustainability. This study aims to investigate how the implementation of business ethics can enhance the effectiveness of CSR within corporate settings. Employing a literature review methodology, the research analyzes academic publications, regulatory frameworks, and corporate reports related to business ethics and CSR. The findings demonstrate that the consistent application of ethical values enriches the meaning and impact of CSR initiatives, improves corporate reputation, and fosters stronger, more sustainable stakeholder relationships. However, challenges such as organizational cultural diversity and insufficient internalization of ethical principles within corporate systems and cultures continue to hinder progress. Consequently, strategic efforts are essential to move beyond treating business ethics as mere normative ideals toward fully embedding them as core values in CSR practices aimed at achieving social and environmental sustainability.